Exchange rates and insulation in emerging markets - Barry Eichengreen; Donghyun Park; Arief Ramayandi; Kwanho Shin (Asian Development Bank (ADB), 2020)
The insulating properties of flexible exchange rates have long been a highly contentious issue in emerging markets - not least in Asian emerging markets. A number of recent theoretical and empirical studies question whether a trade-off exists between rigid exchange rate regimes and insulation from foreign shocks when the degree of international capital mobility is high. On the other hand, Obstfeld, Ostry, and Qureshi (2017) find that countries with flexible exchange rate regimes experience less real and financial instability in the face of global financial volatility. We contribute to this empirical debate by significantly extending their analysis. Overall, our findings are broadly consistent with their results, suggesting that flexible exchange rate regimes are better at insulating emerging markets from external shocks. There are, however, a few subtle differences. In particular, we find somewhat less robust evidence that limited flexibility is enough to insulate emerging markets from shocks.
Keywords: F31; 330; exchange rate; exchange rate regime; fixed; flexible; insulate; intermediate; shock